Estudo da carga de fratura em molares tratados endodonticamente : técnicas restauradoras - Modena, Claudia Freitas de Moura (2020)
Aim: In the first article, the Systematic Review sought previous studies from the last 10 years, which investigated direct restorations in teeth endodontically. In the second article it was evaluate, in vitro, the fracture load of cavity preparations restored with transfixed posts and bulkfill composite resin. Methods: A search was carried out in the health sciences databases (The Cochrane Library, Embase, PubMed-MEDLINE, LILACS, Web of Science, BBO, SCOPUS, Scielo e Science Direct) including articles published until October 2019. Eighty extracted human third molars were randomly divided into eight groups (n=10): G1 – sound teeth; G2 - endodontic treatment + transfixed fiberglass post + composite resin; G3 - transfixed fiberglass post + composite resin; G4 – endodontic treatment + transfixed zirconia posts + composite resin; G5 - transfixed zirconia post + composite resin; G6 – endodontic treatment; G7 – composite resin; G8 – endodontic treatment + composite resin. The specimens were subjected to mechanical cycling with a vertical load of 200 N. Then, the fracture load test was performed in a universal testing machine with a cross-head speed of 1 mm/minute. The types of fracture were analyzed. Results: Based on the results of the Systematic Review, it is concluded that using glass ionomer cement and transfixing fiberglass pins in the dental crown, favor the increased fracture load in endodontically treated teeth. In the in vitro study, according to the Analysis of Variance and Tukey's test (p<0.05), G1 (3666 N) obtained the highest fracture load, not differing significantly from G3 (2856 N) and G5 (2738 N). G7 (2586 N) did not differ significantly from G3, G5 and G2 (1643 N). The lowest fracture load was obtained for G6 (844 N), which did not differ significantly from G2, G4 (1571 N), G8 (1398 N). G3 showed 100% of repairable failures, and G7 obtained 100% of irreparable failures. G1, G2 and G5 obtained 80% of repairable failures. G4 and G6 showed 60% of repairable failures. There were 50% of repairable failures and 50% of irreparable failures in G8. Conclusions: Using glass ionomer cement as a liner for direct restorations improves their longevity. The use of fiberglass or zirconia posts transfixed in MOD preparations, with or without endodontic treatment and restored with composite resin, had similar behaviors regarding the fracture load, with predominance of repairable fractures.